Prolonged tropical forest degradation due to compounding disturbances: Implications for CO2 and H2O fluxes. (25th June 2019) - Brando, Paulo M.; Silvério, Divino; Maracahipes‐Santos, Leonardo; Oliveira‐Santos, Claudinei; Levick, Shaun R.; Coe, Michael T.; Migliavacca, Mirco; Balch, Jennifer K.; Macedo, Marcia N.; Nepstad, Daniel C.; Maracahipes, Leandro; Davidson, Eric; et al.
Abstract: Drought, fire, and windstorms can interact to degrade tropical forests and the ecosystem services they provide, but how these forests recover after catastrophic disturbance events remains relatively unknown. Here, we analyze multi‐year measurements of vegetation dynamics and function (fluxes of CO2 and H2 O) in forests recovering from 7 years of controlled burns, followed by wind disturbance. Located in southeast Amazonia, the experimental forest consists of three 50‐ha plots burned annually, triennially, or not at all from 2004 to 2010. During the subsequent 6‐year recovery period, postfire tree survivorship and biomass sharply declined, with aboveground C stocks decreasing by 70%–94% along forest edges (0–200 m into the forest) and 36%–40% in the forest interior. Vegetation regrowth in the forest understory triggered partial canopy closure (70%–80%) from 2010 to 2015. The composition and spatial distribution of grasses invading degraded forest evolved rapidly, likely because of the delayed mortality. Four years after the experimental fires ended (2014), the burned plots assimilated 36% less carbon than the Control, but net CO2 exchange and evapotranspiration (ET) had fully recovered 7 years after the experimental fires ended (2017). Carbon uptake recovery occurred largely in response to increased light‐use efficiency and reduced postfire respiration, whereas increased water use associated with postfire growth of new recruits and remaining trees explained the recovery in ET. Although the effects of interacting disturbances (e.g., fires, forest fragmentation, and blowdown events) on mortality and biomass persist over many years, the rapid recovery of carbon and water fluxes can help stabilize local climate. Abstract : Postdisturbance recovery of an experimental forest was characterized by delayed postfire mortality of large trees, reduced forest carbon stocks, and the establishment of invasive grasses, pushing a neotropical forest to a new environment. Yet, this highly degraded forests rapidly recovered their capacity to cycle water and to uptake carbon in response to increased water use and light‐use efficiency.